Influencia de los Términos de Intercambio en el Ingreso Doméstico de los Países de la Alianza del Pacífico: Perú, Chile, Colombia y México (1980-2023) - Siancas Escobar, Darwin Alejandro (2025)
The general objective of this study was to determine the impact of the terms of trade on domestic income in the Pacific Alliance countries (Peru, Chile, Colombia, and Mex-ico) from 1980 to 2023. The research was basic, correlational in scope, and used a lon-gitudinal, non-experimental design. Panel data and the statistical software R were used. The most relevant results showed a positive correlation between per capita income and the terms of trade, foreign direct investment (FDI), and external income. These findings support the theory that better trade conditions contribute to increased real income, although they can also generate adverse effects, such as the so-called "re-source curse," if not properly managed.Cryptocurrencies and blockchain technology are reshaping the global financial landscape. Despite regulatory and technical challenges, their ability to enable more transparent, secure, and efficient transactions presents enormous potential. It is essential for policies and regulations to evolve in parallel with these innovations to ensure the sustainable and secure development of the cryptocurrency market.